Medical management of Ogilvie’s syndrome after cesarean delivery: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Neostigmine is a drug commonly used, thus making it a possible second line of treatmentafter conservative methods have failed and surgery is not feasible.Case presentation: A para 3+1 gravida 4 was admitted for elective caesarean delivery because of twoprevious scars at term. She had undergone five previous abdominal surgical procdures. Her antenatalfollow-up was uneventful. Perioperative vital signs were within normal limits, with normal systemicexamination findings. She had abdominal surgical scars, three of which were well healed with no herniaorifices. Leopold’s maneuvers and perioperative laboratory parameters were within normal limits.Intraoperatively, dense adhesions involving the omentum and small gut were attached to the anteriorabdominal and uterine walls along the incision site. The washout of the abdomen and close inspection ofthe omentum confirmed no gut or bladder injury. Postoperatively, she had progressive abdominaldistension with constipation on day three. Abdominal X-ray and computed tomography revealed multipleair-fluid levels and grossly dilated bowel loops. There was no improvement after conservativemanagement, and on the sixth postoperative day, the decision to use neostigmine in an intensive careunit setting was reached. Following a single attempt, success was achieved, and the patient opened herbowels. Subsequently, she regained normal bowel function, and after two months of follow-up, the patientis faring well.Discussion: Ogilvie’s syndrome is defined as colon pseudoobstruction. It is rare (1:1000 admissionsannually) but causes severe morbidity and mortality. The rate is noted to be increasing because ofincreased cesarean delivery rates globally. Diagnosis is based on clinical and imaging findings.Challenges in diagnosis due to challenges in identification and reduced clinician index of suspicion leadto delays in treatment. Neostigmine plays a role in medical management, whereas conservativemanagement has not been effective.